Divinylpyrimidine reagents generate antibody–drug conjugates with excellent in vivo efficacy and tolerability. Issue 12 (19th January 2022) - Walsh, Stephen J.; Omarjee, Soleilmane; Dannheim, Friederike M.; Couturier, Dominique-Laurent; Bexheti, Dorentina; Mendil, Lee; Cronshaw, Gemma; Fewster, Toby; Gregg, Charlotte; Brodie, Cara; Miller, Jodi L.; Houghton, Richard; et al.
Abstract : The development of divinylpyrimidine (DVP) reagents for the synthesis of antibody–drug conjugates (ADCs) with in vivo efficacy and tolerability is reported. Abstract : The development of divinylpyrimidine (DVP) reagents for the synthesis of antibody–drug conjugates (ADCs) with in vivo efficacy and tolerability is reported. Detailed structural characterisation of the synthesised ADCs was first conducted followed by in vitro and in vivo evaluation of the ADCs' ability to safely and selectively eradicate target-positive tumours.